Income Inequality and Carbon Emissions in Post-soviet Nations, 1992–2009 - Jorgenson, Andrew; Schor, Juliet; Giedraitis, Vincentas (Ekonomika, 2018)
We assess the relationship between national-level income inequality and carbon dioxide emissions for a sample of eleven post-Soviet nations during the 1992 to 2009 period. Our findings suggest that both total and per capita emissions are positively associated with income inequality, measured as a Gini coefficient. These results are consistent with analytical perspectives that highlight how income inequality could lead to increases in carbon emissions as well as recent sociological research on income inequality and emissions for samples of nations in other structural and geographical contexts.
Keywords: income inequality; climate change; carbon emissions; ecological economics; environmental sociology; post-Soviet nations; sustainability